Developing Junior High Students’ Writing Skills through WhatsApp Messenger - Hartati, Nur; Nugroho, Andhi Dwi; Subekti, Nanang Bagus (Faculty of Education and Teacher Training of IAIN Palopo, 2022)
The objectives of this study are to investigate the use of WhatsApp messenger to develop students’ writing skills, and to find out the benefits and challenges of the use of WhatsApp messenger to develop students’ writing skills. The design of this study was classroom action research. The researcher used observation, interview, and test to collect the data. In analyzing the data, the researcher followed the procedure of data reduction, data display, and conclusion drawing. The study reports that there was an improvement of the students’ recount text writing skill through scientific approach. In cycle I, the percentage of scores covers steps of rhetorical was (67.50%), grammar (71.25%), vocabulary (66.25%), clarity of meaning (67.50%), and relation between ideas (63.75%). In cycle II, the percentage of scores covers steps of rhetorical was (78.75%), grammar (78.75%), vocabulary (76.25%), clarity of meaning (87.50%), and relation between ideas (81.25%). This study also reports some benefits of using WhatsApp messenger were; the students used their creativity in teaching and learning activity, were interested in teaching and learning processes, and conveyed their assumptions in associating and networking freely. In contrast, it also had challenges in teaching and learning processes. The challenges were; most of students were not enthusiastic to follow teaching and learning of WhatsApp messenger. They must be persuaded to ask questions in questioning phase and they must be directed to be disciplined in the classroom.